2008
DOI: 10.1111/j.1744-7909.2008.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Global Identification of Significantly Expressed Genes in Developing Endosperm of Rice by Expression Sequence Tags and cDNA Array Approaches

Abstract: Rice endosperm plays a very important role in seedling germination and determines the qualities of rice grain. Although studies on specific gene categories in endosperm have been carried out, global view of gene expression at a transcription level in rice endosperm is still limited. To gain a better understanding of the global and tissue-specific gene expression profiles in rice endosperm, a cDNA library from rice endosperm of immature seeds was sequenced. A cDNA array was constructed based on the tentative un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The homogenate was centrifuged at 10,000 g at 4°C for 20 min, and the supernatant was used as the crude enzyme extract. Ten μl of each extract was applied onto a native-polyacrylamide gel and native PAGE/staining of BE isozyme activity was performed as described previously ( Yamanouchi and Nakamura, 1992 ). Native PAGE was performed on a slab gel prepared of 7.5% (w/v) resolving gel with 3.3% (w/v) stacking gel using a modified version of the method described by Davis (1964) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The homogenate was centrifuged at 10,000 g at 4°C for 20 min, and the supernatant was used as the crude enzyme extract. Ten μl of each extract was applied onto a native-polyacrylamide gel and native PAGE/staining of BE isozyme activity was performed as described previously ( Yamanouchi and Nakamura, 1992 ). Native PAGE was performed on a slab gel prepared of 7.5% (w/v) resolving gel with 3.3% (w/v) stacking gel using a modified version of the method described by Davis (1964) .…”
Section: Methodsmentioning
confidence: 99%
“…The roles of individual BE isozymes in starch biosynthesis in rice endosperm have been examined by many groups worldwide using mutants and transformants prepared from both japonica -type and indica -type rice cultivars. It has been reported that although the relative activities of BEI, BEIIa, and BEIIb in both cultivars are reported approximately 60–80%, 10–20%, and 10–20%, respectively ( Yamanouchi and Nakamura, 1992 ), the impacts of the three BE isozymes on the starch synthesis and structure greatly differ among them ( Nakamura, 2002 ). Mutations in the BEIIb gene resulted in the amylose-extender ( ae ) phenotype of the caryopses, which had a floury appearance and reduced weight ( Mizuno et al, 1993 ; Nishi et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…SBEIIa and SBEIIb share ∼80% sequence identity (Mizuno et al, 1992; Nakamura et al, 1992). SBEIIa is prodominantly expressed in leaves, while SBEIIb is mainly expressed in the rice grains (Yamanouchi and Nakamura, 1992; Ohdan et al, 2005; Yamakawa et al, 2007). SBEIIb is a major SBEII isoform in the rice endosperm (Yamanouchi and Nakamura, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…SBEIIa is prodominantly expressed in leaves, while SBEIIb is mainly expressed in the rice grains (Yamanouchi and Nakamura, 1992; Ohdan et al, 2005; Yamakawa et al, 2007). SBEIIb is a major SBEII isoform in the rice endosperm (Yamanouchi and Nakamura, 1992). To further increase the AC, one can direct the starch synthesis toward amylose production through either overexpressing a suitable GBSS ( Waxy ) allele (Hanashiro et al, 1996; Itoh et al, 2003), or suppressing the expression of enzymes involved in amylopectin biosynthesis (Morell and Myers, 2005; Regina et al, 2006; Rahman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies focused on various metabolic pathways such as nutrient partitioning. In rice, different technologies including EST [15], [16], cDNA [16] and DNA microarray [14], [17], [18], and deep sequencing [19] have been applied to analyze the transcriptional profiles in seeds. In most of these studies (except in 14), RNAs were collected from seed tissues at single time point of multiple genotypes/cultivars.…”
Section: Introductionmentioning
confidence: 99%